Collaborative networks and thematic trends of research on the application of complementary and alternative medicine in cancer patients: A bibliometric analysis. (November 2019) - Yang, Weimei; Hao, Xinying; Qu, Jia; Wang, Lan; Zhang, Meng; Jiang, Yun; Liu, Yu
Abstract: Background: and purpose: Complementary and Alternative Medicine(CAM) has been greatly used in cancer patients. This research aimed to explore the research priorities of CAM for cancer patient's treatment. Methods: Web of Science(WoS), HistCite, BibExcel, GunnMap and VOSviewer were used to extract and visualize information. Results: 2768 articles published in 789 journals were indexed in the WoS from 1989 to 2018. The USA(n = 1009) and Technion-Israel Institute Technology(n = 58) were the most prolific country and institution, respectively. Keywords co-occurrence analysis indicated that the research hotspots around the world formed five clusters, so did the author co-citation analysis. The research priorities of the top-five countries, the top-three prolific authors and the co-citation core authors were also discussed, which reveals the differences and similarities among them. Conclusion: This study delineates a framework for better understanding the situational use of CAM in cancer patients, which could help health care workers to prioritize and organize future research. Highlights: The USA dominates the literature related to CAM in cancer patients, followed by Germany, Canada, UK, China. Keywords co-occurrence analysis indicated that the research hotspots around the world formed five clusters. Breast cancer is the most concerned type of cancer, and the focus on other types of cancer varies from country to country. Research content mainly includes symptom management, website information management, evidence-based information support, etc.